Analisis Swot Sebagai Strategi Meningkatkan Daya Saing Pada Bisnis Usaha Batik (Studi Kasus: Industri Batik Syn-Surakarta) - Putri, Elysa Paramitha, Much. Djunaidi ST., MT, Ahmad Kholid Al Ghofari, ST. MT (2015)
Batik SYN is an industry that produces silk batik, batik printing and batik combination. Batik SYN is located at Jl. Kolonel Sugiyono 50B Nayu Cengklik, Nusukan Surakarta. The purpose of this study are to identify factors internal and external business marketing strategies, and also formulatingthe appropriate alternate business strategy, in order to improve Batik SYN's competitiveness using marketing mix method. This study uses SWOT analysis and Marketing Mix. Using this SWOT analysis,there are several alternative strategies for making a good decision to run that will be able to generate. The next step is determining the STP of research objects determine market segmentation, target consumers, and the position or actions to build and communicate the benefits of a special subject of the product in the market. The final step of this research is analyzing the marketing mix. The results using SWOT analysis is in a position of growth by using the strategy of SO (Strength Opportunies). Further to the analysis of STP, using demographic segmentation by targeting female sex, age 45-55 years, self-employment jobs, and income > 5 million. As for positioning, Batik SYN have better product quality compared with other similar competitors. As for the proposal of the right marketing strategy for Batik SYN conducted by analysis of the marketing mix through product, namely the addition of product variants and the type of fabric, the establishment of quality standards, and good packaging of the products it sells. As for the price, Batik SYN can provide discounts and commissions for the provision of intermediary agents who participated promote products Batik SYN. Furthermore, the distribution is done by conducting cooperation to the intermediary agent who can deliver products of Batik SYN quickly and timely. The most recent promotion is done by individual sales, sales promotion, and publicity. Keywords: Marketing Mix, Marketing Strategy, STP, SWOT